Of Women Tech Pioneers and Tiny Experts of Ingenuity - Kjartansdóttir, Skúlína Hlíf; Hjartarson, Torfi; Pétursdóttir, Svava (Frontiers in Education, 2020)
TThis paper presents findings from a collective case study focusing on the efforts of a grassroots team of seven pioneering women: teachers, IT consultants, and tech enthusiasts. The team was formed to introduce, encourage, and establish makerspaces in the Icelandic compulsory school system by educating and supporting teachers and young students (6 to 15 years) as makers and advocates of maker culture. All seven team members have developed or supported different models of makerspaces in their area of work and offered guidance to other educators. Our research examines learning on a personal, relational and institutional level, reviewing values and practices of participants and what characterizes their social interactions, agency and empowerment in relation to making. It introduces new models of pedagogy, often supported by school leadership and social media action facilitating the development of making and maker culture. It attempts to map how makerspaces can be integrated into school practice in alignment with curricular objectives to support diverse engagements, digital literacies and creative design skills. Our findings further reveal how an all-women team has taken agency and through collaborative actions, collective creativity and self-empowerment managed to overcome challenges and provide leadership in this emergent field in Icelandic school practice.